Analisis Sektor Unggulan dalam Pembangunan Daerah di Kabupaten Lampung Barat - Maulana, M. Fadhli; Prasaja, Ahmad Syukron (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
The regional economic development planning for West Lampung Regency must align with public interests. Economic growth is measured through the Gross Regional Domestic Product (GRDP) from 2018 to 2021, with trade, industry, and agriculture sectors being the priorities. The LQ (Location Quotient) and DLQ (Dynamic Location Quotient) methods are used to identify key sectors. Economic development priorities should focus on these potential sectors.